Homeroom Teacher Strategy in Improving Learning Media Literacy during Covid-19 Pandemic - Arif, Muhamad; Munfa'ati, Kusnul; Kalimatusyaroh, Mei (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
The existence of the Covid-19 pandemic requires that all elements change from the economy, health and education. The role of teachers in education is the main key to successful learning, however, during the Covid-19 pandemic, online-based learning made teachers learn to improve learning media literacy, so that they could provide solutions to a fun learning process. In this research, we want to find answers about how classroom teachers' strategies in increasing media literacy during the Covid-19 pandemic. This research used a qualitative method with a case study approach. The primary data source for the researcher was all class teachers in both Madrasah Ibtidaiyah. Collecting data using three techniques, observation, interviews and documentation. Analysis of the research data using the analysis of Miles and Huberman. Combined with the Quin Patton data validity test, namely data triangulation. The results showed that Madrasah Ibtidaiyah Al-Azhar Menganti Gresik increased media literacy individually and institutionally. Meanwhile, Madrasah Ibtidaiyah An-Nur Junwangi Sidoarjo individually. For homeroom teacher, learning media at Madrasah Ibtidaiyah Al-Azhar Changing Gresik Zoom, Google Meet, Canva, Youtube and Whatsapp media. Meanwhile, in Madrasah Ibtidaiyah An-Nur Junwangi Sidoarjo, the learning process is still focused on using the Whatsapp Group. In addition, there are obstacles for classroom teachers in improving learning media literacy, including lack of internet quota, and infrastructure.